Optimasi Pupuk Organik Cair Dan Npk Terhadap Beberapa Sifat Kimia Tanah Dan Hasil Jagung Di Lahan Tercemar Limbah Clarifier - Muhammad Agus Mulyana; Emma Trinurani Sofyan; Pujawati Suryatmana (Faculty of Agriculture University of Singaperbangsa Karawang, 2018)
Degradation of rice fields ecosistem from industrial waste contamination has caused harmful impact for farmingsustainability and developing crop production. This study aimed to investigate the effect of various treatment of NPKand Liquid Organic Fertillizer towards several chemical compound in the soil and Vegetatif and generative Growth ofSweet Corn (Zea mays) in clarifier contaminated rice fields from industrial waste. The experiment was conducted in thecontaminated clarifier ricefield of PT PUPUK KUJANG CIKAMPEK from June to August 2017. Randomized blockdesign with nine single treatment, that is A = 0 NPK and 0 ml/L POC, B = 1 NPK and 0 ml/L POC, C = 1 NPK and 2,5ml/L POC, D = 1 NPK and 5 ml/L POC, E = 1 NPK and 7,5 ml/L POC, dan F = 1 NPK and 10 ml/L POC, G = 3/4NPK and 5 ml/L POC, H = 1/2 NPK and 5 ml/L POC, I = 0 NPK and 5 ml/L POC each with three replicates was usedas experimental design in this research. The result showed that the application NPK and Liquid Organic fertilizer hassignificant effect on increasing several chemical compound in the soil and Vegetatif and generative Growth of SweetCorn (Zea mays).Keywords : NPK, Liquid Organic Fertillizer